2017
DOI: 10.1016/j.ica.2017.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Zinc binding with l-dopa peptides

Abstract: The combination of zinc dyshomoeostasis and oxidative damage has been linked to a number of human disease pathologies. A common pathway of oxidative damage centers on tyrosine with the generation of 3,4-dihydroxyphenylalanine (L-dopa). Once formed this catecholic moiety can be involved in metal binding. Herein, an L-dopa residue is incorporated into a peptide designed to adopt a -hairpin configuration. Variation of the cross strand partner to L-dopa introduces an aromatic pair to enhance structure. Mass spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Since there is no histidine in these ZCPs, and indole group was concluded not to be the zinc binding site (Figure 4A), free carboxyls at the C-terminus were found to be the primary zinc binding sites. They are essential to chelate divalent metal ions to form stable peptide-zinc complexes [51,53].…”
Section: Resultsmentioning
confidence: 99%
“…Since there is no histidine in these ZCPs, and indole group was concluded not to be the zinc binding site (Figure 4A), free carboxyls at the C-terminus were found to be the primary zinc binding sites. They are essential to chelate divalent metal ions to form stable peptide-zinc complexes [51,53].…”
Section: Resultsmentioning
confidence: 99%
“…The causes of zinc deficiency include insufficient zinc intake, inadequate absorption, increased demand, and increased excretion, which is attributed to continuous administration of chelating drugs; levodopa being a known drug having this effect. Drugs with ≥2 hydroxide ions, such as levodopa, may chelate zinc and stabilize it by forming a five-or six-membered ring [16]; these chelated compounds are in turn excreted in the urine, which may result in zinc deficiency. Previous studies of serum zinc concentration in drug chelates have already been investigated in rats.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been reported that some drugs possess zinc‐chelating capability and may be the reason for drug‐related taste diabetes mellitus disturbances (Tomita & Yoshikawa, ). It has been reported that L‐dopa may induce zinc deficiency (Tomita & Yoshikawa, ), which chelates zinc (Veldkamp, Tubergen, Swartz, DeVries, & Tatko, ). Prior to this study, no reports showed serum zinc levels decreasing progressively with LCIG treatment.…”
Section: Discussionmentioning
confidence: 99%